2015
DOI: 10.1002/art.38966
|View full text |Cite
|
Sign up to set email alerts
|

Bcl‐2 Antagonists Kill Plasmacytoid Dendritic Cells From Lupus‐Prone Mice and Dampen Interferon‐α Production

Abstract: Objective. Interferon-␣ (IFN␣)-producing plasmacytoid dendritic cells (PDCs) are implicated in the pathogenesis of systemic lupus erythematosus (SLE). IFN␣-related genes are highlighted among SLE susceptibility alleles and are characteristically expressed in the blood of patients with SLE, while in mouse models of lupus, PDC numbers and IFN␣ production are increased. This study was undertaken to investigate the effects of inhibitors that selectively target different antiapoptotic molecules on the survival of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 59 publications
3
55
0
Order By: Relevance
“…This finding was not surprising given the dysregulation of IFN in human systemic lupus erythematosus (SLE) (41,42) and in NZW/B lupus model mice (ref. 43 and references therein). Because recent studies have reported Treg modulation by IFN (reviewed in ref.…”
Section: Resultsmentioning
confidence: 99%
“…This finding was not surprising given the dysregulation of IFN in human systemic lupus erythematosus (SLE) (41,42) and in NZW/B lupus model mice (ref. 43 and references therein). Because recent studies have reported Treg modulation by IFN (reviewed in ref.…”
Section: Resultsmentioning
confidence: 99%
“…S2H). Conversely, ABT-199 significantly reduces IFN-α production by pDCs, including pDCs from lupus-prone (NZB/NZW F1) mice (34).…”
Section: Discussionmentioning
confidence: 96%
“…This differential dependence on BCL-2 advocates the use of BCL-2 selective antagonist BH3 mimetic drugs for treating pDC-associated diseases (34). Refined understanding of how the survival of the distinct DC subsets is regulated is therefore expected to provide valuable insight into the pathogenesis of inflammatory diseases and guide the development of effective therapeutic interventions for such diseases.…”
Section: Discussionmentioning
confidence: 99%
“…A study evaluating the dependence of plasmacytoid dendritic cells (pDCs) and conventional DCs (cDCs) on antiapoptotic proteins revealed that pDCs had higher levels of BCL-2 compared with cDCs, and were selectively killed when cultured in vitro with venetoclax, highlighting their dependence on BCL-2 for survival (124). Using a similar chemical parsing approach, the BCL-2 inhibitors venetoclax and ABT-737 were found to selectively kill mouse and human pDCs but not cDCs, and synergized with glucocorticoids to kill activated pDCs (125). These findings indicated that BCL-2 antagonists may be attractive candidates for treating pDC-associated diseases such as BPDCN.…”
Section: Future Considerations and Conclusionmentioning
confidence: 99%